Retention, Employee Engagement, and Workload in the Building Wire Production Line at PT. Kabelindo Murni Tbk: Exploring the Role of Employee Status - Baharsyah, Ilham Baihaqi; Mujiono, Sherina Anggraini; Muallifah, Siti; Tyas, Ari Anggarani Winadi Prasetyoning (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study aimed to influence employment status on employee retention, employee engagement, and workload at PT. Kabelindo Murni Tbk in the Building Wire production line. Using a qualitative approach and case study design, data was collected through interviews, observation, and documentation. The results show that employees with PKWTT (permanent employment status) have higher engagement and motivation compared to PKWT (contract) employees. PKWTT employees feel more involved in decision-making and more valued, while PKWT employees feel limited by their contract status, which leads to lower loyalty and retention. Although both groups face significant workloads, PKWTT employees are more flexible in managing their time and tasks. These findings provide insights into management to design policies that support increased employee engagement and retention, as well as more efficient workload management.